The Finite Absorption Time (FAT) concept en route to PBPK modeling and pharmacometrics - Macheras, Panos; Tsekouras, Athanasios A. (JOURNAL OF PHARMACOKINETICS AND PHARMACODYNAMICS, 2023)
The concept of Finite Absorption Time (FAT) for oral drug administration is set to affect pharmacokinetic analyses, Physiologically-based Pharmacokinetics simulations, and Pharmacometrics.